2009
DOI: 10.4067/s0034-98872009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Esófago negro secundario a esofagitis necrotizante aguda: Reporte de un caso clínico

Abstract: Black esophagus due to acute necrotizing esophagitis. Report of one case Acute esophageal necrosis, which presents as a black esophagus on endoscopy, is an uncommon occurrence. It is defined as a dark pigmentation of the esophagus associated with histologic mucosal necrosis. We report a 75-year-old men who developed black esophagus due to acute esophageal necrosis caused by septicemia. The patient had a favorable evolution (Rev Méd Chile 2009; 137: 672-4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
10
0
6
Order By: Relevance
“…Wallberg et al reported similar favorable outcome of BE in a 75-old-year patient with sepsis 4 , which is a major cause of systemic inflammatory response and circulatory failure. Common clinical features are dyspepsia, epigastralgia, hematemesis, melena, and vomiting, but the diagnosis suspicion of BE during endoscopy must be further confirmed by histological data.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…Wallberg et al reported similar favorable outcome of BE in a 75-old-year patient with sepsis 4 , which is a major cause of systemic inflammatory response and circulatory failure. Common clinical features are dyspepsia, epigastralgia, hematemesis, melena, and vomiting, but the diagnosis suspicion of BE during endoscopy must be further confirmed by histological data.…”
mentioning
confidence: 56%
“…Worth of note, only about a hundred cases of this entity were reported since the first description in 1990 [1][2][3][4] ; notwithstanding, published necropsy data are suggestive that BE may be under diagnosed and/or under reported 2,5 . The aim of the present paper is to enhance the suspicion index about BE, which will have better outcome if early diagnosis and precocious treatment can be accomplished.…”
mentioning
confidence: 99%
See 3 more Smart Citations